Serat Wulangreh: Mengislamkan Jawa Melaui Pendekatan Budaya - Muslih, Mustopa (Universitas Darussalam Gontor, 2024)
Pakubuwana IV combined Islamic teaching and Javanese culture on Serat Wulangreh without eliminating the core value of Islamic teaching its result. Pakubuwana IV used the Javanese language as a communication tool to distribute his message of advice through The Macapat song. Substantially, Wulangreh is Islamic teaching taken from The Al-Quran and Hadith which cover the aspects of divinity, law, ethics, virtue, and social relationship aspect. Although Serat Wulangreh employs local language and culture, it displays identifiable pure Islamic teaching. The teachings on Wulangreh are the forms of acculturation of Islam and Javanese culture. They are applicable in a pluralistic society as a form of multiculturalism emphasizing equality and equity within a diverse and dynamic community (tribes, ethnicities, cultures, and religious beliefs